Achalasia cardia in an infant - were we too late? - Bhutani, Jyoti; Rengan, Vinayak; Lora, Sawai S.; Pansari, Vishnu; Sharma, J. N. (International Journal of Contemporary Pediatrics, 2022)
Achalasia cardia is a motility disorder where there is aperistalsis of the body of the esophagus and failure of lower esophageal sphincter relaxation. This manifests as a functional gastroesophageal junction obstruction. This disorder is rare and has a prevalence of 10 in 100,000 population. It has a peak incidence between 30-60 years of age. The incidence in the pediatric population is very low and is even rarer in infants. Here we present a case of achalasia cardia in a 9-month-old male infant weighing 3.1 kilograms. The child had complaints of regurgitation of milk, non-projectile vomiting, fever and cough for the past 3 months along with failure to thrive. He was treated for bronchopneumonia initially and then evaluated with a barium swallow. The barium swallow revealed a hold-up of contrast in the distal esophagus along with a typical bird-beak appearance. Definitive surgical intervention was being planned. However, the child aspirated and expired. Did we delay the procedure? Were we too late? These questions continue to make us self-introspect on the management of infantile achalasia cardia. The paucity of available publications and data is a major roadblock in management.